Improving Teacher Practices With Children Under Five: Experimental Evidence From the Mississippi Buildings Blocks. (February 2019) - Arteaga, Irma; Thornburg, Kathy; Darolia, Rajeev; Hawks, Jacqueline
Background: The literature on the effects of teacher coaching in early childhood (EC) education programs is underdeveloped but emerging. Using the theory of action in professional development as our theoretical framework, we hypothesize that active coaching improves teaching methods and creates a more effective classroom environment for enhancing children's learning and skills. Objectives: This study evaluates the effects of the Mississippi Building Blocks (MBB) program, an EC intervention with a strong emphasis on supervisor and coaching training. Research design: We conduct a randomized controlled experiment in which data were collected at baseline, midpoint (Month 3), and postintervention (Month 6) in 24 preschool classrooms in Mississippi. Subjects: The experiment included 195 preschoolers, of which 95 were in classrooms led by teachers who received coaching (treatment) and 100 were in classrooms without coaching (control). Measures: We measured child's emergent language and literacy, fine motor skills, gross motor skills, print language skills, problem-solving, math skills, and socioemotional development. Results: We find that MBB coaching led to substantial improvements in child outcomes relative to the control group, particularly in gross motor skills, print language skills, and socioemotional development. We also find some evidence that MBB coaching improved math skills, though these estimates are on the margin of statistical significance. Finally, a mediator analysis indicates that improvements in the classroom learning environment brought about by MBB coaching improved child outcomes. Conclusions: Our findings suggest that an intensive form of classroom coaching for teachers leads to significant gains in child outcomes.